CONFLICTS AND DISPUTES FOR LAND AND WATER: THE GERAIZEIROS PEOPLE OF CORRENTINA-BA AND THE EXPANSION OF AGRIBUSINESS IN THE MATOPIBA’S CERRADO - Jesus, Priscila Barbosa de; Almeida, Maria Geralda de (Geosaberes; Vol 13 (2022)DO - 10.26895/geosaberes.v13i0.1085, 2022)
The article in question discusses the idea of rural development using as an example the experience of the geraizeiros peoples of Correntina-BA when dealing with the effects of the expansion of agribusiness in the Matopiba’s Cerrado. As a methodology, bibliographic review and fieldwork in the highlighted region were used. In addition to the discussion on the idea of rural development, the text also addresses the conflicts over water and land in Correntina-BA, the attempt to criminalize the groups of re-existence and, finally, highlights the perception and reports of the subjects who are directly involved. However, it is understood that the search for rural development has been based solely on economic bias and as a result there is an intensification of inequalities existing in these spaces.